From Porfirio to Huerta: the problems with the United States seen from Spain - Sevilla Soler, Rosario (Revista de Historia Social y de las Mentalidades, 2013)
The US intervention in the Mexican Revolution could not be viewed well from Spain, which, in addition to maintaining close relations with Mexico during the Porfiriato, still felt "hurt" by US interference in Cuba. Starting from this premise, this work aims to show the vision that the Spanish population -and more specifically the Sevillian population- had of the role played by the United States in the first phases of the revolutionary process, through the press and the writings of some Spanish intellectuals and Latin Americans.
Keywords: Porfiriato; Mexican revolution; North American intervention